Type 3 secretion system as an anti-Pseudomonal target - Horna G. (2021)
Type 3 secretion systems (T3SSs) are a series of mechanisms involved in bacterial pathogenesis. While Pseudomonas aeruginosa only possess one T3SS, it plays a key role in the virulence of P. aeruginosa virulence. This finding suggests that T3SS impairment may be an alternative for antimicrobial agents, allowing P. aeruginosa infections to be directly combated avoiding antimicrobial pressure on this and other microorganisms. To date, different approaches have been proposed, including T3SS inhibition, vaccination strategies, development of anti-T3SS antibodies and gene silencing. © 2021 Elsevier Ltd